HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN SELF EFFICACY MENYUSUI PADA IBU PRIMIPARA DI WILAYAH KERJA PUSKESMAS MAMAJANG KOTA MAKASSAR - Andi Tenri Abeng; Andi` Wahyuni (Jurnal Berita Kesehatan, 2021)
Self Efficacy of breastfeeding Mothers is one of the important factors that influence breastfeeding. Breastfeeding is an unparalleled way of providing the ideal food for healthy growth and development, and the health of mothers and babies can strengthen the inner bond between mother and baby. This study aims to examine the relationship Knowledge and family Support With Self Efficacy Breastfeeding On Ibu Primipara in the Working Area of Mamajang Health Center Makassar This type of research is descriptive analytic research with Cross sectional study approach. Population referred to in this study were all postpartum primipara women who have given birth in the birth room mamajang a number of 68 people, obtained 41 respondents samples with Technique of Sampling Non Probability Sampling is Accidental Sampling. The results show after bivariate analysis from Chi-Square test obtained p (0,000) < α (0,05) hence hypothesis conclusion no rejected and alternative hypothesis accepted that there is relation knowledge with Self Efficacy suckle. Results of research can be seen from Chi-Square test results obtained p (0,001) < α (0,05) hence hypothesis conclusion no rejected and alternative hypothesis accepted that there is relation of family support with Self Efficacy breastfeeding. From the results of research is expected for the community, especially families in providing support, in the family especially husband, parents help mothers to be able to breastfeed comfortably so that the milk produced maximum.